Seeds of Genus Cassia as Possible Sources of Induitiual Gums - Farooqi, M. I. H.; Kapoor, V. P.; Islam, Gohar (Indian Forester, 1978)
Seeds samples from 20 Cassia species have been chemically studied. Several of them including the seeds of Cassia alota have been found to possess better or equal properties with those presently used as gum source like guar and Carob seeds and, therefore, some of the Cassia seeds can be utilized as source of industrial gums.